Application of Various Computer Tools for the Optimization of the Heat Pump Heating Systems with Extraction of Low-Grade Heat from Surface Watercourses - Sychov, A. (2019)
A number of computer tools have been applied to solve optimization issues of the heat pump heating systems with extraction of low grade heat from surface watercourses are described. Among them: 3D modeling in CAD KOMPAS-3D, calculations using numerical methods and programming elements in MathCAD, measurements using a specially designed computer monitoring system. The example of a novel design of the submersible water-brine heat exchanger is presented. Â© 2019, Springer Nature Switzerland AG.